"Bad jobs": a case study of toilet attendants. Issue 3 (13th March 2019) - Adriaenssens, Stef; Hendrickx, Jef
Abstract : Purpose: The purpose of this paper is to contribute to the knowledge of precarious and low-quality jobs with the study of toilet attendants, an ideal typical case of low-wage manual service workers who are excluded from secure wages, decent working conditions, and employment protection. Design/methodology/approach: An extensive survey with standardized questionnaires ( n =107) and in-depth interviews ( n =10) of toilet attendants in Belgian towns, mostly Brussels and Ghent. Results are compared to the work quality of low-skilled workers, and the within-group position of necessity workers is analysed. Findings: Toilet attendants definitely occupy "bad jobs", measured by the higher prevalence of informal and false self-employed statuses, more intense work-life conflicts and verbal aggression from clients, and a lower job satisfaction. In all these respects, they perform worse than other low-skilled workers. Concurrently, there is a strong within-group divide between necessity workers and those who see the job as an opportunity. Despite a similar job content, necessity workers less often earn a decent wage, suffer more from customer aggression, lack social support and pleasure from work. Mechanisms related to self-selection and the absence of intrinsic rewards explain these in-group differences. Originality/value: This contribution indicates, first, that job insecurity spills over into poor working conditions, work-life conflicts, and customer aggression. Furthermore, it documents that jobs are not necessarily bad in themselves, but become problematic when taken up by people with too few choices and too pressing socio-economic needs. Problems of sub-standard jobs are not merely job problems but problems of workers in a certain position.